Monoclonal antibodies specific for carcinoembryonic antigen produced by hybridoma technology - Horestein, A. L.; Glait, H. M.; Koss, Amalia; Capalbo, E; D’ Orio, E.; Olivari, A. J. (1986)
Fil: Horestein, A. L. Comisión Nacional de Energía Atómica; Argentina